Correlation between hemoglobin levels of mothers and children on exclusive breastfeeding in the first six months of life - Rosa de Fátima da Silva Vieira Marques; José Augusto de Aguiar Carrazedo Taddei; Tulio Konstantyner; Affonso Celso Vieira Marques; Josefina Aparecida Pellegrini Braga (Brazilian Society of Pediatrics, 2016)
Objective: To evaluate the correlation between hemoglobin levels of mothers and their children on exclusive breastfeeding in the first six months of life. Methods: Cross‐sectional study with 221 binomials (mother-child) enrolled in a breastfeeding support program, who were stratified into six groups according to the children's age group. The sample consisted of children born at term with normal weight, with no neonatal complications and whose mothers did not have anemia or infectious disease at the time of data collection. Interviews were carried out with the mothers, blood was collected by peripheral venipuncture from mothers and children, and children's anthropometric data were assessed. Pearson's correlation coefficients between the hemoglobin levels of mothers and children were calculated. Six multiple linear regression models were adjusted with regression coefficient estimates, considering as statistically significant associations with p ≤ 0.05. Results: The correlation coefficients of hemoglobin levels of mothers and children ranged from 0.253, at three months, to 0.601, at five months. The hemoglobin level of mothers was correlated with the hemoglobin level of their children at four months (r = 0.578) and at five months (r = 0.601). In the adjusted multiple linear regression, the regression coefficients were higher at four months (β = 1.134; p = 0.002) and at five months (β = 0.845; p < 0.001). Conclusion: These findings allow for the conclusion that there is a correlation between the hemoglobin of mothers and the hemoglobin of their children on exclusive breastfeeding in the first six months of life.